PENERAPAN METODE INFERENSI FUZZY TAKAGI-SUGENO-KANG UNTUK PREDIKSI PRODUKSI GETAH PINUS DI KPH KEDU SELATAN - , AULIA MARHADI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The production of timber is currently very significant its role in the forestry sector. The most significant non timber forest product is pine resin that produced by Pinus merkusii. For a better components, required the estimating system that is accurate. Now many methods used, but it has not qualified accuracy. One of the methods that can be applied is a Takagi- Sugeno-Kang (TSK) to study the possibility of the application of TSK method on estimating the production of resin and provide alternative production of pine resin estimating model. This research used the application of fuzzy Takagi-Sugeno-Kang logic. Which is in the process of identification model system of TSK fuzzy influenced by the variable premise combination, premise parameters and consequent parameters. Steps of estimating the production of resin using the application of fuzzy logic consisting of the literature cited step, the modelling step, analysis of the reliability of model step, the selection of the best model step and phase the withdrawal of the conclusion step. Estimating of the pine resin production calculated using a fuzzy TSK method with combinations of variable and assemblage, then regression of analysis method as a comparison. To know the reliability of every model we used the calculation of RMSE value. On a fuzzy TSK method, the combination of 22 RMSE obtained value amounting to 15,1215 and RMSE value regression analysis of 21,9397. It showed that combination 22 can use since the value of RMSE smaller than the value RMSE of regression analysis. The value of this shows that the model of TSK have a chance to be applied and will have kind of accuracy that is getting better if found a combination of premise variable, premises parameters, and the optimum of consequent parameters.